Artikel Personal Branding Mahasiswa Ui Asal Bengkulu Dalam Pemanfaatan Instastory: Studi pada Instagram @samikn_ - Kemas Musyadat Kholiq; Eni Khairani (STAI Bumi Silampari, 2025)
This study aims to analyze personal branding through the Instagram account @samikn_ belonging to a University of Indonesia student from Bengkulu by utilizing the InstaStory feature. Using Peter Montoya's (2003) personal branding theory and McNally's (2012) personal brand characteristics, this study applies a descriptive qualitative approach through content analysis of InstaStory publications over a certain period of time. Semi-structured interviews and documentation analysis are also used as supporting data. The results show that @samikn_ has successfully implemented Montoya's eight personal branding principles, including activeness in organizations (The Law of Specialization), leadership in public speaking and preserving Bengkulu culture (The Law of Leadership), and authentic personality in motivation and a healthy lifestyle (The Law of Personality). In addition, he emphasizes uniqueness through volunteer activities (The Law of Distinctiveness), maintains visibility through consistent uploads (The Law of Visibility), combines personal values ??with the built image (The Law of Unity), demonstrates persistence in communication (The Law of Persistence), and has a positive impact on the environment (The Law of Goodwill). @samikn_'s personal brand also meets McNally's criteria: unique, relevant to the younger generation, and consistent.